A new subfamily of Feaellidae (Arachnida, Chelonethi, Feaelloidea) from Southeast Asia - Judson, Mark L. I. (Zootaxa, 2017)
The first extant representatives of the pseudoscorpion family Feaellidae from Southeast Asia are described. Cybella n. gen. is proposed for Cybella deharvengi n. sp. (type species), collected from an isolated limestone hill in Hon Chong Province, Vietnam, and C. bedosae n. sp., found in a limestone cave in Kampuchea, Cambodia. Cybella species seem to be restricted to karst formations and are probably troglophilic. The type localities of the two known species are threatened by quarrying activities, these being particularly pressing in the case of C. deharvengi n. sp. Cybella shows important differences from other Feaellidae that require a modification of the familial diagnosis and justify the erection of a new subfamily, Cybellinae. The discovery of this group provides insights into the evolution of the unusual morphology of the family, notably concerning the pleural plates of Feaellinae, which are lacking in Cybellinae. The smaller sclerites of the pleura of Pseudogarypidae and Feaellidae are shown to be muscle apodemes, which provide an additional synapomorphy for Feaelloidea. Two types of coxal spines, termed primary and secondary, are distinguished in Feaelloidea, based on the presence of a lumen within the primary spines and its absence in secondary spines. The new morphological term atrial plate is proposed for a sclerotized plate of the male genitalia, extending between the lateral rods and the lateral apodemes. Claims that the internal genital setae of males of non-chthonioid pseudoscorpions are secretory are reviewed and found to lack support. Additional information concerning the fossil genus Protofeaella Henderickx, 2016 is provided, based on an adult male in amber from the Cretaceous (lowermost Cenomanian) of Myanmar. Protofeaella shares with Cybella the absence of pleural plates and the antiaxial position of the chemosensory setae of the movable chelal finger. However, it differs from both Cybellinae and Feaellinae in having relatively long chelal fingers that lack a tuberculate basal tooth, both of which are interpreted as symplesiomorphic states within Feaellidae. Protofeaella is therefore provisionally treated as a stem-group feaellid and not assigned to a subfamily. The existence of a Cretaceous member of the Pseudogarypidae is noted in the mid-Cretaceous (late Albian‒early Cenomanian) of Germany, representing the oldest record of this family.